2021
DOI: 10.1108/jmp-10-2020-0537
|View full text |Cite
|
Sign up to set email alerts
|

The role of events and affect in perceived organizational support: a within-person approach

Abstract: PurposeThe purpose is to understand how affective events employees experience at work, and emotions those events elicit, influence within-person fluctuations in perceived organizational support (POS). The authors explore the possibility of socioemotional needs as a boundary condition of the effects. They integrate affective events theory with organizational support theory to develop their arguments.Design/methodology/approachUsing a diary study method, 55 working adults responded to three surveys per day for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…First, previous studies have confirmed that employee recognition is a very effective management tool that can promote better employee performance. Based on previous studies, our research found that employee recognition not only directly promotes recognized employees ( Garr, 2012 ) but also has a positive effect on the bystanders who witness the recognition, enabling them to perceive better organizational justice, enhance their sense of wellbeing at work ( Woznyj et al, 2021 ), and thus, healthy work environment and happiness fulfillment effectively improve employees’ performance while they have much confidence, energy, and psychological safety ( Abuelhassan and Algassim, 2022 ). The results show that employee recognition is also beneficial to shaping a fair organizational atmosphere.…”
Section: Discussionmentioning
confidence: 80%
“…First, previous studies have confirmed that employee recognition is a very effective management tool that can promote better employee performance. Based on previous studies, our research found that employee recognition not only directly promotes recognized employees ( Garr, 2012 ) but also has a positive effect on the bystanders who witness the recognition, enabling them to perceive better organizational justice, enhance their sense of wellbeing at work ( Woznyj et al, 2021 ), and thus, healthy work environment and happiness fulfillment effectively improve employees’ performance while they have much confidence, energy, and psychological safety ( Abuelhassan and Algassim, 2022 ). The results show that employee recognition is also beneficial to shaping a fair organizational atmosphere.…”
Section: Discussionmentioning
confidence: 80%